(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This Study Was Carried Out In Peru, With The Purpose Of Determining Which Economic Variables Influence The Behavior Of The Peru-Chile Trade Balance. The Method Used For The Research Is Non-Experimental, And The Type Of Research Was Correlational - Causal. The Main Conclusion Was That The Factors That Explain The Peruvian Trade Balance With Respect To Chile Are: Peru’s Gdp, Chile’s Gdp, The Bilateral Real Exchange Rate And The Trade Agreements With Chile. Likewise, Peru’s Gross Domestic Product, Bilateral Real Exchange Rate And Trade Agreements With Chile Are Inversely Related To The Trade Balance, While Chile’s Gross Domestic Product Is Directly Related To The Trade Balance. On The Other Hand, The Long-Term Equation Indicates That If Peru’s Gross Domestic Product Increases, The Balance Of Trade Balance Decreases; If Chile’s Gross Domestic Product Increases, It Causes An Increase Of 0.03% In The Balance Of Trade Balance. Finally, If The Bilateral Real Exchange Rate Depreciates, This Improves The Balance Of Trade Balance, Which Demonstrates The Presence Of The J-Curve Phenomenon For The Peru-Chile Case.